"Shahó and the Power of Place". Issue 1 (28th October 2021) - Leysath, Maggie; Galan, Rachel
Abstract: On April 13, 2019, an EF3 tornado demolished the traditional Caddo grass house and the Caddo Mounds State Historic Site museum with approximately 80 people inside. This occurred on Caddo Days, an annual event designed for Caddo people to share their culture with the surrounding community. In July 2019, survivors, community members, and Caddo people gathered for a weekend in which representatives of the International Coalition of Sites of Conscience facilitated art and ritual activities to process the events of April 13 and tell the story as a part of the history of the site and the Caddo people.